Efektivitas Manajemen Sumber Daya Manusia Dalam Meningkatkan Mutu Pendidikan - Saiful Afor; Fajeri Arkiang; Maruf Ishak Ola; Siti Ida Yanti (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
This research is qualitative field research that takes place at Madrasah Tsanawiyah Baburahman Aloindonu, Northwest Alor District, Alor Regency. The research subjects are Head of Madrasah, Deputy Head of Curriculum, Deputy Head of Public Relations, Educators who have long served, Educators who have recently served, Educators of English subjects, and Class VII, VIII, and IX students. Collecting data using interviews, observation, and documentation. Testing the validity of the data using source triangulation. The data analysis technique that the researcher uses is the data obtained and then compiled and describes the results of interviews and documentation according to what they are, data reduction, verification, and conclusions, after which validation is carried out. The results of the study show that: 1) the Head of Madrasah in carrying out the management process uses various stages, namely recruitment, selection, development, maintenance, and compensation of human resources but has not been realized optimally; 2) The factors that influence human resource management are the strong commitment of the Madrasah Principal in carrying out the functions of human resource management and the high enthusiasm of educators and education staff to transfer their abilities and skills; 3) Always get support from the foundation and the surrounding community. So that until now human resource management can still function properly, although it still needs to be improved. The quality of education is obtained from the results of the assessment of the National Accreditation Board for Schools/Madrasah which is rated C / quite good.